Dominância financeira: capital fictício e capitalismo contemporâneo - Guimarães, Leonardo Ferreira (2014)
The current reality of capitalism is widely perceived as dominated by the financial dynamics. Also, the occurring crisis in recent years has been interpreted in the same way. Basically, the initial motivations of this research are these. The treatment of these motivations, took place in the field of Marx's thought. The central objective of this dissertation is to investigate, within the said field, the senses in which one can speak of dominance and autonomy (basic prerequisite for dominance) of that which comprises loosely as a financial phenomenon. The outline of the research was focused on the following authors: François Chesnais; Gérard Duménil; Dominique Lévy; Eleutério Prado; Reinaldo Carcanholo; Paulo Nakatani; Maurício Sabadini (these last three authors are part of what is called here the Victory School) besides, of course, Karl Marx . It is noteworthy that the influence of Victory School is central to this work. Faced with this framework of authors, we sought to theoretically specify the term finance through the development of other categories and more precise concepts such as interest-bearing capital, fictitious capital and parasitical speculative capital. The research sought to understand the connections that these categories establish among themselves and determine in which way occurs the financial autonomy of the phenomenon. For this, we needed a chapter to address methodological issues, which were worked from the notion of social forms , taking inspiration from the book Alysson Mascaro Estado e forma política, as well as some of the aforementioned authors